The Relationship Between Physical Activity Levels of the School of Physical Education and Sports Students and Their Life Satisfaction - Mine Koç; Hande İnan (Journal of Educational Issues, 2024)
This study aims to investigate the correlations between the physical activity levels of students who study sports sciences and their life satisfaction levels according to a number of variables. The study group was composed of 212 students—100 of whom were female and 112 of whom were male—who attended Physical Education and Sports School of Adıyaman University in 2020-2021 academic year. The participants were given the international physical activity questionnaire (Craig et al., 2003) and satisfaction with life scale (SWLS) (Diener & Griffin, 1985) along with personal information form (IPAQ-SF) online. As a result, no correlations were found between physical education and sports school students’ levels of physical activities and their life satisfaction. Accordingly, the BMI average for the female students (x̄ = 20.31) was found to be significantly lower than the average for the male students (x̄ = 23.68). The inactive students’ average (x̄ = 21.61) and the average of the students who were very active (x̄ = 21.37) were significantly higher (p < 0.01). On the other hand, no significant differences were found in the participants’ levels of physical activity or in their life satisfaction levels according to types of sports and gender (p > 0.05). In conclusion, it may be stated that physical activities do not affect university students’ life satisfaction but that they eliminate their problems of overweight and that those activities reduce the average for BMI in positive ways and thus resulted in healthier individuals.